1999
DOI: 10.2527/1999.774846x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic variants of the heart fatty acid-binding protein gene on intramuscular fat and performance traits in pigs.

Abstract: In order to find genetic markers to improve the meat quality of pigs by breeding we studied the relationship between variation in the heart fatty acid-binding protein (H-FABP) gene (FABP3) and intramuscular fat (IMF) content. To estimate the effect of H-FABP, pigs from two Duroc populations were selectively mated in such a way that at least two genotypes were present in each litter. In total, data from 983 pigs and pedigree information from three preceding generations were analyzed. Offspring were tested for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
93
4
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(125 citation statements)
references
References 17 publications
18
93
4
10
Order By: Relevance
“…The H-FABP gene is, according to our results, associated with IMF and MA, but not with BF. This result is not concordant with the first reports which described a main effect of this gene on BF [8], although more recent works have described this association with only IMF [9,13,14]. Moreover the effect of the gene on IMF in our population was independent of BF content, since the introduction of BF as the covariate in the model did not modify the results, contrarily to those reported by Gerbens et al [8].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The H-FABP gene is, according to our results, associated with IMF and MA, but not with BF. This result is not concordant with the first reports which described a main effect of this gene on BF [8], although more recent works have described this association with only IMF [9,13,14]. Moreover the effect of the gene on IMF in our population was independent of BF content, since the introduction of BF as the covariate in the model did not modify the results, contrarily to those reported by Gerbens et al [8].…”
Section: Discussioncontrasting
confidence: 93%
“…Polymorphisms in this locus have been associated with fatness traits in the Duroc breed and Meishan crossbred pigs [8,9] and in Duroc × Landrace pigs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Alasnier and colleagues in rabbits [12] failed to show any strict association between the relative proportion of oxidative fibers in various muscles and their respective fat content. Genetic variants of FABP have been associated with muscle lipid content in pigs [37], but their involvement at the protein level remains unclear [38]. Finally, in line with our results, LPL activity has been negatively associated to marbling in cattle [39].…”
Section: Discussionsupporting
confidence: 78%
“…Johansson et al [36] reported relatively small differences in fatty acid composition for pigs with and without the RN -allele. In pigs, polymorphisms in the H-FABP gene have been associated with variability in intramuscular fat content, largely independent of backfat thickness [25,26], but to our knowledge no reports on the possible changes in fatty acid composition are available yet. Interestingly, in a QTL mapping study using an F 2 cross between Iberian × Landrace pigs, Pérez-Enciso et al [61] concluded that the metabolism and(or) deposition rate of linoleic acid is under (partial) control of a QTL on chromosome 4, and that the effect of the QTL was not an artifact caused by the differences in backfat thickness.…”
Section: Porkmentioning
confidence: 99%